Pharmacologic Targeting of BET Proteins Attenuates Hyperuricemic Nephropathy in Rats - Xiong, Chongxiang; Deng, Jin; Wang, Xin; Shao, Xiaofei; Zhou, Qin; Zou, Hequn; Zhuang, Shougang (Frontiers in Pharmacology, 2021)
Hyperuricemia is an independent risk factor for renal damage and promotes the progression of chronic kidney disease. In this study, we investigated the effect of I-BET151, a small-molecule inhibitor targeting the bromodomain and extraterminal (BET) proteins, on the development of hyperuricemic nephropathy (HN), and the mechanisms involved. Expression levels of bromodomain-containing protein 2 and 4, but not 3 were increased in the kidney of rats with HN; administration of I-BET151 effectively prevented renal dysfunction, decreased urine microalbumin, and attenuated renal fibrosis as indicated by reduced activation of renal interstitial fibroblasts and expression of fibronectin and collagen I in HN rats. Mechanistic studies show that I-BET151 treatment inhibited transition of renal epithelial cells to a mesenchymal cell type as evidenced by preservation of E-cadherin and reduction of vimentin expression. This was coincident with reduced expression of TGF-β1 and dephosphorylation of Smad3 and ERK1/2. I-BET151 was also effective in inhibiting phosphorylation of NF-κB, expression of multiple cytokines and chemokines, and infiltration of macrophages to the injured kidney. Although there were increased serum levels of uric acid and xanthine oxidase, an enzyme that catalyzes production of uric acid, and decreased expression of renal organic anion transporter 1 and 3 that promote urate excretion in the model of HN, and reduced expression levels of urine uric acid, I-BET151 treatment did not affect these responses. Collectively, our results indicate that I-BET151 alleviates HN by inhibiting epithelial to mesenchymal transition and inflammation in association with blockade of TGF-β, ERK1/2 and NF-κB signaling.